PEMETAAN POLA SEBARAN DAN SPASIAL LOKASI BANGUNAN INDOMARET DI KOTA SURABAYA BAGIAN TIMUR BERBASIS SISTEM INFORMASI GEOGRAFI - barafanny, riris enggar (Universitas Negeri Surabaya, 2023)
East Surabaya City, as one of the major cities in Java Island from its economic and trade development, in East Surabaya City there are 111 Indomaret outlets. This research is expected to identify the distribution pattern of Indomaret in East Surabaya City. This study tries to relate the distribution pattern of Indomaret in East Surabaya City with nearest neighbor analysis. The analysis is used to determine the distribution pattern of Indomaret in East Surabaya. From the results of the identification of distribution patterns based on the nearest neighbor analysis, it was found that the distribution pattern of Indomaret in East Surabaya City tends to be clustered, which is indicated by the nearest neighbor T/index value of 0.25 which is close to 0.